STRATEGI MANAJEMEN HOTEL SIMA KUTA DALAM PEMULIHAN OPERASIONAL PASCA PANDEMI COVID-19 - Baiq Febri Izzati Isnaini; Rizal Kurniansah; I Ketut Purwata (Journal Of Responsible Tourism, 2023)
This research was motivated by a government policy that decided to limit activities that caused crowds and crowds caused by the Covid-19 pandemic. This has made hotel management have to look for other strategies so that their service companies can survive during the Covid-19 pandemic. The purpose of this study was to find out how the strategy carried out by Hotel Sima Kuta Lombok in maintaining the lodging and hotel services business during the Covid-19 pandemic. The type of research carried out by the author is field research with the research location of the Sima Kuta Lombok Hotel, which is located in Kuta, Kuta Village, Pujut District. Methods of data collection using interviews, observation and documentation. While the data analysis technique used is descriptive qualitative analysis using SOAR analysis. SOAR analysis is used to formulate alternative strategies that can be carried out by a company. The results show that through strategic stages and SOAR analysis shows the strategy carried out by Sima Kuta Lombok Hotel is quite effective in business development but sees market opportunities that are still open along with many emerging competitors with Similar efforts require additional strategies by utilizing the strengths they have.